Use of Mobile Devices to Access Point-of-Care Information Resources by Doctors of Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria. Issue 3 (2nd July 2016) - Adegbilero-Iwari, Idowu; Adegbilero-Iwari, Oluwaseun Eniola
ABSTRACT: Mobile technologies such as smartphones and tablets have gained popularity in the Nigerian telecommunication industry recently, so much so that Nigeria ranks as the fastest growing telecommunication market. Despite this, there seems to be a dearth of studies on the clinicians' use of mobile devices to access point-of-care (POC) information in Nigeria. This article seeks to investigate how medical doctors are meeting their point-of-care information needs through these mobile devices. A specially designed questionnaire was used to elicit information; data were analyzed using the SPSS statistical tool and the results were discussed. The study found that 74.29% of the doctors possessed smartphones and accessed POC information resources using these devices. However, 54.28% were found to use laptops to access POC information resources. Smartphones (57.14%) are the preferred means of accessing POC information resources, while lack of Internet connectivity (57.14% and lack of data subscription (54.29%) were the major limitations confronted by doctors using mobile devices to access POC information resources.